ANALYSIS OF FACTORS AFFECTING POVERTY IN NORTH SUMATERA PROVINCE (CASE STUDY IN 33 DISTRICT / CITY) - Avandi, Yudistira (Universitas Negeri Medan, 2019)
The equitable poverty reduction in North Sumatera became one of the unresolved issues until now. The decreasing of poverty percentage in the last five years in North Sumatera can not represent the level of public welfare. In fact , in 2013, there were 22 out of 33 districts in North Sumatera which have the poverty percentage more than ten percent and known as hardcore poverty. The highest poverty percentage was found in North Nias and Gunung Sitoli by 30.94 %, while the lowest was found in Deli Serdang by 4.71 %. This research stated the problem â€œHow is the influence of the economic growth, level of education, and the minimum regional wages toward the level of poverty in North Sumatera Province? The objective is to analyze the influence of economic growth, the level of education and the minimum wages toward the poor population in North Sumatera Province. This research used 165 samples that spread in 33 districts in North Sumatera from 2009 until 2013 with panel data and using Fixed Effect Model Method.Â The result of the Ordinary Least Square Method (LOS) through the multiple linear regretion estimated model showed that the economic growth and the minimum regional wages had negative influence, while the level of education had positive influence toward poverty in North Sumatera. The coefficient of determination (R2) is 0.948157 which means the variable of economic growth, minimum regional wages and level of education can define the poverty in North Sumatera by 94.82 %, and 5.18 % defined by other economic variables outside the model.